An experimental approach to the investigation of the effectiveness of translation in bilingual retention - Yeo, Zi Sing (Nanyang Technological University, 2022)
Growing up in a multi-lingual and multi-cultural environment, under a top-tier education system, Singaporeans are known for their bilingual capability. Yet gaps in the language education system are starting to widen as more and more Chinese Singaporean young adults’ Chinese competency has dropped due to the lack of usage. This is reflected in the recent Singapore Household Survey, where 48.3% of Singaporeans speak English at home (Department of Statistics Singapore, 2021). Many studies have also found that the environment has a significant influence on an individual’s bilingual competencies. However, participants of these studies were generally young children, and there is a lack of studies investigating bilingual competencies among young adults. This study hence seeks to investigate if translation training can be a form of intervention to help young adults to improve their bilingual and linguistic competencies. The focus of this study is on the effectiveness of translation training and the investigation of additional factors that can potentially impact an individual’s bilingual competency. The findings of this study were derived from an experimental test of two groups of participants. The results show that participants from the Experiment Group who went through translation training made less translation errors compared to those in the Control Group who did not. The overall translation quality of the Experiment Group was also significantly better than the Control Group. Although there was insufficient data available to draw a conclusive analysis for a few of the factors, this study has shown that translation training is beneficial in retaining or improving bilingual competencies. It is hoped that further research on the correlation between translation training and bilingual competence can be extensively carried out by more researchers.